Comparing Plasticity of Response to Perceived Risk in the Textbook Example of Convergent Evolution of Desert Rodents and Their Predators; a Manipulative Study Employing the Landscape of Fear - Bleicher, Sonny S.; Kotler, Burt P.; Brown, Joel S. (Frontiers in Behavioral Neuroscience, 2019)
Foragers process information they gain from their surroundings to assess the risk from predators and balance it with the resources in their environment. Measuring these perceived risks from the perspective of the forager can produce a heatmap or their “fear” in the environments, a so called “landscape of fear” (LOF). In an intercontinental comparison of rodents from the Mojave and Negev Deserts, we set to compare families that are used regularly as examples of convergent evolution, heteromyid and gerbilline respectively. Using a LOF spatial-analysis on data collected from common garden experiments in a semi-natural arena we asked: 1) Do all four species understand the risk similarly in the exact same physical environment; 2) Does relative relation between species affect the way species draw their LOFs, or does the evolutionary niche of a species have greater impact on its LOF?; and 3) Does predator facilitation between vipers and barn owls cause similar changes to the shape of the measured LOFs. For stronger comparative power we mapped the LOF of the rodents under two levels of risk: low risk (snakes only) and high risk (snakes and barn owls). We found concordance in the way all four species assessed risk in the arena. However, the patterns observed in the LOFs of each rodent family were different, and the way the topographic shape of the LOF changed when owls were introduced varied by species. Specifically, gerbils were more sensitive to owl-related risk than snakes and at the opposite correct for heteromyids. Our findings suggest that the community and environment in which a species evolved has strong impacts on the choices animals make. We also conclude, that given the homogenous landscape we provide in our arena and the non homogenous patterns of LOF maps, risk assessment can be independent of the physical conditions under which the animals find themselves.